Sound Symbolism Facilitates Long-Term Retention of the Semantic Representation of Novel Verbs in Three-Year-Olds - Katerina Kantartzis; Mutsumi Imai; Danielle Evans; Sotaro Kita (Languages, 2019)
Previous research has shown that sound symbolism facilitates action label learning when the test trial used to assess learning immediately followed the training trial in which the (novel) verb was taught. The current study investigated whether sound symbolism benefits verb learning in the long term. Forty-nine children were taught either sound-symbolically matching or mismatching pairs made up of a novel verb and an action video. The following day, the children were asked whether a verb can be used for a scene shown in a video. They were tested with four videos for each word they had been taught. The four videos differed as to whether they contained the same or different actions and actors as in the training video: (1) same-action, same-actor; (2) same-action, different-actor; (3) different-action, same-actor; and (4) different-action, different-actor. The results showed that sound symbolism significantly improved the childrens’ ability to encode the semantic representation of the novel verb and correctly generalise it to a new event the following day. A control experiment ruled out the possibility that children were generalising to the “same-action, different-actor„ video because they did not recognize the actor change due to the memory decay. Nineteen children were presented with the stimulus videos that had also been shown to children in the sound symbolic match condition in Experiment 1, but this time the videos were not labeled. In the test session the following day, the experimenter tested the children’s recognition memory for the videos. The results indicated that the children could detect the actor change from the original training video a day later. The results of the main experiment and the control experiment support the idea that a motivated (iconic) link between form and meaning facilitates the symbolic development in children. The current study, along with recent related studies, provided further evidence for an iconic advantage in symbol development in the domain of verb learning. A motivated form-meaning relationship can help children learn new words and store them long term in the mental lexicon.